Natural polymers - John, Maya J.; Thomas, Sabu (RSC green chemistry series, 2012)
Examines the characterization, life cycle assessment and new sources of natural fibres and their potential as a replacement for synthetic fibres in industrial applications. It then explores the important advancements in the field of wool, silk, spidersilk and mussel byssus fibres.